PENGARUH MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Stella Stella; Misdalina Misdalina; Marhamah Marhamah (Universitas Muhammadiyah Bengkulu, 2019)
ABSTRACTThe formulation of this research was the effect of Auditory Intellectually Repetition (AIR) model learning toward the matematical problem solving abilities students eighth grade of SMP Negeri 53 Palembang. This experiment’s research used Posttest-Only Control Design with sample of 62 students were taken by using cluster sampling technique. A experiment class got treatment by using Auditory Intellectually Repetition (AIR) model learning and a control class got a treatment by using conventional model learning with each class numbering 31 students. Technique for collecting the data used test technique. In analyzing the data, the writter usedIndependent Sample t-Test with 5% significant level. The conclusion of this research was there were significant influence between Auditory Intellectually Repetition (AIR) model learning toward the matematical problem solving abilities students to the eighth grade students of Junior High School 53 of Palembang.Keywords: AIR learning model, conventional learning model, matematical problem solving abilities